Outcome of Neonates with Meconium Aspiration Syndrome at the University Hospital of the West Indies, Jamaica: A Resource-Limited Setting - Panton, L.; Trotman, H. (American Journal of Perinatology, 2017)
Aim To determine the outcome of neonates with meconium aspiration syndrome (MAS) at the University Hospital of the West Indies over a 5-year period.Methods This was a retrospective, descriptive study looking at all inborn neonates with MAS. Data on maternal and neonatal demographics, clinical course, and outcome were recorded. Descriptive analyses were performed.Results The incidence of MAS was 10 per 1,000 live births. Fetal distress was documented in 32 (30%) cases. Thirty-two (30%) neonates were postdates at the time of delivery and 32 (30%) neonates were delivered by emergency cesarean section. Seven (6%) neonates required mechanical ventilation and 16 (15%) required bubble continuous positive airway pressure. Seven (6%) neonates had hypoxic ischemic encephalopathy, 5(5%) had persistent pulmonary hypertension of the newborn, and 1 (4%) had a pneumothorax. There was a 1% mortality rate. Thick meconium beneath the cords, grunting, and hypoxia on admission were independent predictors of disease severity.Conclusion The incidence of MAS was similar to that of other resource-limited settings; however, the disease spectrum was milder with lower morbidity and mortality.
Keywords: meconium aspiration syndrome; meconium; outcome in MAS; predictors of MAS